CD24HICD38HI TRANSITIONAL B CELLS AND CD9 AS NEW BIOMARKER OF LONG-TERM HUMAN LUNG ALLOGRAFT SURVIVAL - DURAND, Maxim; BROSSEAU, Carole; MAGNAN, Antoine; BROUARD, Sophie (2020)
The present invention relates to an in vitro method for determining the risk of occurrence of chronic lung graft dysfunction in a human subject comprising: a) measuring the level of CD9 + B cells in a blood sample of the subject, b) comparing the level of CD9 + B cells measured at step a) with one or more reference values of the level of CD9 + B cells, and c) determining the risk of occurrence of chronic lung graft dysfunction in the said subject from the comparison performed at step b).